2020
DOI: 10.1016/j.ebiom.2020.102813
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Protein Kinase C β Contributes to the Pathogenesis of Preeclampsia by Activating Autophagy

Abstract: Background: Preeclampsia is a devastating hypertensive disorder of pregnancy with unknown mechanism. Recent studies have considered abnormal autophagy as a new cellular mechanism for this disorder, while little is known about how autophagy is specifically involved and what factors are implicated. Here, we report a previously unrecognized preeclampsia-associated autophagic regulator, PKCb, that is involved in placental angiogenesis. Methods: PKCb levels were evaluated by quantitative real-time PCR, western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…This pool of lysosomes is central to the degradation and recycling of macromolecules delivered by endocytosis and autophagy. This increase in lysosomes in E-PE agrees with numerous reports of elevated autophagy in preeclamptic placentae ( Oh et al, 2008 ; Kalkat et al, 2013 ; Akaishi et al, 2014 ; Gao et al, 2015 ; Melland-Smith et al, 2015 ; Akcora Yildiz et al, 2017 ; Hutabarat et al, 2017 ; Ausman et al, 2018 ; Zhao et al, 2020 ). Lysosome biogenesis is regulated by a lysosome-to-nucleus signaling mechanism that involves TFEB.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This pool of lysosomes is central to the degradation and recycling of macromolecules delivered by endocytosis and autophagy. This increase in lysosomes in E-PE agrees with numerous reports of elevated autophagy in preeclamptic placentae ( Oh et al, 2008 ; Kalkat et al, 2013 ; Akaishi et al, 2014 ; Gao et al, 2015 ; Melland-Smith et al, 2015 ; Akcora Yildiz et al, 2017 ; Hutabarat et al, 2017 ; Ausman et al, 2018 ; Zhao et al, 2020 ). Lysosome biogenesis is regulated by a lysosome-to-nucleus signaling mechanism that involves TFEB.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, Nakashima et al (2020) reported that autophagolysosomal degradation is defective in preeclamptic placentae due to reduced TFEB and LAMP1 expression. Although their finding may explain the build up of protein aggregates in preeclamptic placentae, it clashes with the generally accepted view of elevated autophagy flux in preeclamptic placentae ( Oh et al, 2008 ; Kalkat et al, 2013 ; Akaishi et al, 2014 ; Gao et al, 2015 ; Melland-Smith et al, 2015 ; Akcora Yildiz et al, 2017 ; Hutabarat et al, 2017 ; Ausman et al, 2018 ; Zhao et al, 2020 ). Unfortunately, the authors did not verify their findings at the ultrastructural level (TEM is the gold standard for surveillance of organelles and autophagy) and mainly focused on extravillous trophoblasts while we surveyed the villous trophoblast layers.…”
Section: Discussionmentioning
confidence: 70%
“…Studies of autophagy in preeclampsia provide conflicting roles of this homeostatic mechanism on preeclampsia development and progression [ 7 ]. In this issue of EBioMedicine , Zhao and colleagues report the results of a hybrid study using clinical placental samples and a mouse model of preeclampsia to identify a novel preeclampsia-associated regulator of autophagy [ 8 ]. The regulation of autophagy in preeclampsia is an area of research that has been increasing in interest over the past several years and the results reported in this featured article sought to identify a new target with therapeutic potential.…”
mentioning
confidence: 99%
“…The regulation of autophagy in preeclampsia is an area of research that has been increasing in interest over the past several years and the results reported in this featured article sought to identify a new target with therapeutic potential. Analysis of mRNA levels and protein expression of protein kinase C isoform β (PKCβ) in control and preeclamptic patient placentas demonstrated significantly lower expression of PKCβ in preeclampsia [ 8 ]. Furthermore, analysis of PKCβ mRNA expression using the Gene Expression Omnibus (GEO) dataset confirmed suppression of PKCβ in preeclampsia.…”
mentioning
confidence: 99%
See 1 more Smart Citation